Enhanced sinterability and electrical properties of Bi2O3-added Ba0.85Ca0.15Zr0.1Ti0.9O3ceramics - Piyaporn Jaimeewong (2018)
© 2017 Taylor & Francis Group, LLC. The ceramics of Bi2O3-added Ba0.85Ca0.15Zr0.1Ti0.9O3or BCZT-xBi (where x = 0.005, 0.01, 0.02 and 0.1 mol fraction) were fabricated from sol-gel auto-combustion derived BCZT and commercial Bi2O3powders. In this study, BCZT-0.02Bi ceramic sintered at 1200°C for 2 h was found to be the optimum composition with high relative density and homogeneous microstructure. The temperature at maximum dielectric constant (Tmax) of this sample was near room temperature, rendering a high dielectric constant value (∼1653). Frequency dependence of Tmaxsuggested the relaxor behavior which was also supported by slim ferroelectric hysteresis loops. Since a relatively large breakdown voltage (> 70 kV/cm) was observed, the BCZT-0.02Bi ceramic could be a potential lead-free electrostrictive/piezoelectric material for actuator applications.